Contemporary heroes and heroines - Browne, Glenn J.; Browne, Kevin O.; Browne, Ray Broadus; Straub, Deborah Gillan (Gale Research, 1990)
Brief profiles of more than 100 contemporary men and women from all walks of life whose activities reflect heroic traits.